Art, science and speculation: Kibira atlas of ecological fabrications Abstract - Teixeira, Bruna; Venturelli, Suzete (DAT Journal, 2026)
This study presents initial results from the doctoral research project “Atlas Kibira de Fabricações Ecológicas – Poética Cuir e Outros Ensaios Transmasculinos”, which operates at the intersection of scientific imagination and contemporary art. It centers on Kibira as a case study, a fictional cuir settlement created from the vitality of transimaginative worlds. The article presents an artistic proposal that uses images generated through artificial intelligence and digital painting, applied to compositions of animation, digital art, and speculative sculpture, as an invitation to think with the impossible in order to denounce the real. It begins with a broad theoretical contextualization of the Atlas, addressing queer ecology and works on data visualization. It then analyzes the territorial and archaeofictional context of Kibira, describing geofuga and the local rock art findings of the Murintaquara Tradition and the Cliroca style. Finally, it considers how a cuirized investigation can challenge traditional discriminatory systems against the LGBTQIAPN+ population and expand the visual frontiers of art.